Virtual Factory for Manufacturing Process Visualization - Zhong, Yongmin; Shirinzadeh, B. (Monash University, 2008)
This paper presents an integrated methodology for building a virtual factory. This methodology integrates discrete event simulation directly to 3D animation with its novel methods that analyze and convert discrete simulation results into animation events to trigger 3D animation. In addition, it constructs a 3D animation framework for the visualization of discrete event simulation. This framework supports the reuse of both the existing 3D animation objects and behaviour components, and allows the rapid development of new 3D animation objects by users with average programming skills. This methodology has been implemented with the software component technology. Results from its practice in an electronics assembly factory are also provided in the paper to demonstrate the performance of this new methodology.